Comment on Barckhausen et al., 2014 – Evolution of the South China Sea: Revised ages for breakup and seafloor spreading. (January 2015) - Chang, Jih-Hsin; Lee, Tung-Yi; Hsu, Ho-Han; Liu, Char-Shine
Abstract: We re-examined the cessation of the South China Sea seafloor spreading by using radioactive dating and fossil assemblage of the ETO, and the Te-derived age. The youngest available age for the fragment of the South China Sea is ∼15 Ma and is more consistent with those suggested by previous studies. Moreover, recent IODP Expedition preliminary results suggested that the hemipelagic claystone layer stratigraphically bounded by igneous sequences of massive lava flow rock is Early Miocene in age. Therefore, the previous interpretations are more inclusive than those provided by Barckhasen et al. (2014) and indicate that a slow spreading ridge was more plausible to have occurred during the seafloor spreading of the South China Sea.